Comparison of differential metabolites in brain tissue of aged marmosets and serum of elderly patients after prolonged anesthesia - Zhang, Fengwei; Mao, Haoli; Zhu, Jiao; Zhou, Ren; Zhang, Lei; Jiang, Hong (Frontiers in Molecular Neuroscience, 2023)
Objective: To compare the differential metabolites in the brain tissue of aged marmosets after long-term anesthesia (≥ 6 h) and the serum of elderly patients by metabolomics methods. Results: The changes in lactate and xanthurenic acid in the serum of elderly patients were consistent with those in the brain tissue of aged marmoset monkeys, that is, lactate was up-regulated and xanthurenic acid was down-regulated. However, serum levels of 5-methylterahydrofolic acid and leucine were down-regulated in elderly patients after anesthesia. In contrast, 5-methylterahydrofolic acid and leucine levels were up-regulated in the prefrontal cortex of aged marmosets compared with control marmosets. Furthermore, aminoacyl-transfer ribonucleic acid biosynthesis, glycolysis/gluconeogenesis, valine, leucine, and isoleucine biosynthesis and degradation, pentose phosphate pathway, one carbon pool by folate, and purine and pyruvate metabolism were significantly enriched in the prefrontal cortex of aged marmosets and serum of elderly patients after surgery. Conclusion: The changes of serum metabolites in elderly patients are not exactly the same as the metabolic changes of brain tissues in aged marmosets.The metabolic changes in serum lactate and xanthurenic acid levels can reflect brain tissue metabolism. The enrichment pathways of differential metabolites in the serum of elderly patients and the brain tissue of aged marmosets were partially the same.